The Effect Of Group Guidance On Social Phobia For Inpatients Of Drug Rehabilitation In Tampan Mental Hospital (Rsj) - Rahmad, Rahmad; Netrawati, Netrawati; Neviyarni, Neviyarni; Hariko, Rezki (Educational Guidance and Counseling Development Journal, 2025)
This study aims to analyze the effect of group guidance on social phobia for drug rehabilitation inpatients at the Tampan Mental Hospital (RSJ) Pekanbaru City. The sample consisted of 30 respondents taken using purposive sampling technique. The independent variable in this research is Group Guidance, while the variable related to this research is Social Phobia. This research uses quantitative methods with a survey approach. Furthermore, from the results of the t test analysis it is known that there is a significant influence between the variable (X) group guidance on the variable (Y) social phobia. This is proven by the results of the t test calculation of 5.491.  Meanwhile, ttable with df 28 of 5% is 2.048 which can be concluded that (Ha) is accepted and (H0) is rejected. From the analysis of research data, it was also obtained that the magnitude of the influence of group guidance on social phobia for drug rehabilitation inpatients was 51.8%. This is based on an efficiency of 51.8% with a positive influence, which means that the higher the group guidance provided, the higher the resilience of drug rehabilitation inpatients. Meanwhile, 48.2% are factors that influence the variable (Y) Social Phobia for drug rehabilitation inpatients which were not examined by researchers.